Hip extension during the come-out of multiple forward and inward pike somersaulting dives is controlled by eccentric contraction of the hip flexors - Kong, P. W. (Journal of Sports Sciences, 2010)
A modelling approach was used in the present study to investigate the role of the hip muscles during the come-out of forward and inward multiple somersaulting dives in a pike position. A planar two-segment model was used to simulate the somersault and come-out of three commonly performed dives from a 3-m springboard: forward two-and-one-half somersault pike dive (105B), forward three-and-one-half somersault pike dive (107B), and inward two-and-one-half somersault pike dive (405B). Three simulations were run for each dive: (1) hip angle was constrained to be constant, (2) hip torque was removed after 0.1 s, and (3) hip angle was constrained to a typical come-out time history used by elite divers. Simulation results indicated that hip flexion torque was required both to maintain a rigid pike position during somersault (range = 205.5-282.3 Nm) and to control the hip extension movement during the come-out (peak torque range = 355.8-548.1 Nm) in forward and inward multiple somersaulting dives. Coaches and divers should be aware that dry-land exercise drills producing hip extension movement by concentric actions of the hip extensor muscles do not replicate the neuromuscular control during the come-out of fast rotating dives.